Answer:
x = -5, and y = -6
Step-by-step explanation:
Suppose that we have two equations:
A = B
and
C = D
combining the equations means that we will do:
First we multiply both whole equations by constants:
k*(A = B) ---> k*A = k*B
j*(C = D) ----> j*C = j*D
And then we "add" them:
k*A + j*C = k*B + j*D
Now we have the equations:
-x - y = 11
4*x - 5*y = 10
We want to add them in a given form that one of the variables cancels, so we can solve it for the other variable.
Then we can take the first equation:
-x - y = 11
and multiply both sides by 4.
4*(-x - y = 11)
Then we get:
4*(-x - y) = 4*11
-4*x - 4*y = 44
Now we have the two equations:
-4*x - 4*y = 44
4*x - 5*y = 10
(here we can think that we multiplied the second equation by 1, then we have k = 4, and j = 1)
If we add them, we get:
(-4*x - 4*y) + (4*x - 5*y) = 10 + 44
-4*x - 4*y + 4*x - 5*y = 54
-9*y = 54
So we combined the equations and now ended with an equation that is really easy to solve for y.
y = 54/-9 = -6
Now that we know the value of y, we can simply replace it in one of the two equations to get the value of x.
-x - y = 11
-x - (-6) = 11
-x + 6 = 11
-x = 11 -6 = 5
-x = 5
x = -5
Then:
x = -5, and y = -6
Answer:
Step-by-step explanation:
Part A - Where did Phillip make a mistake? Justify your answer using complete sentences.
Use order of operation (PEMDAS)
He should multiply 8 x 4 first
Part B - Solve the expression correctly in the space below.
(5 x 9) - 8 x 4
= 45 - 32
= 13
Part C - Use the same rules of order of operations to solve the expression (8-4) +9 x 3. Explain your steps as you solve it.
(8-4) + 9 x 3
Step 1: 4 + 9 x 3 (Subtract in the parenthesis first)
Step 2: 4 + 27 (Multiply 9 x 3)
Step 3: 31 (Add)
Answer:
5 min person wit 10 min person
5 min person wit 20 min person and 5 min person back
5 min person wit 25 min person and 5 min person back
5 min person need to slow down ea. time
The probability that a child with a speaking part is chosen randomly would be 2:5.